A non-printed integrated-circuit textile for wireless theranostics - Yuxin Yang (Nature Portfolio, 2021)
The typical approach to electronics is to integrate sensors, power units, and controlling components on a printed circuit board (PCB). Here, the authors demonstrate a self-powered and fully integrated combination of sensors and controlling components that is woven, rather than integrated onto a PCB, allowing for wearable health monitoring.”